Level of Reading Comprehension of Scientific Texts for Chemical Concepts in the Ninth Grade for Science Textbook - Omar, Sozan; ALotaibi, Reem (Jordan Journal of Educational Sciences, 2014)
The aim of this study was to measure the reading comprehension levels for chemistry concepts in science textbook of ninth grade. A descriptive approach was adopted to accomplish the study. Participants were (253) female students chosen randomly from ninth grade in public schools in Riyadh. A test for the reading comprehension for chemistry concepts included in ninth grade science textbook was created and tested for validity and stability. A semi-structured interview was conducted for a sample of (6%) of all participants (15 students). Results indicated that the level of reading comprehension was low in general, hence, the highest mean was the direct understanding level and the lowest was the critical understanding level. The study suggested that attention should be given to develop reading comprehension skills including the skills of reading photos and diagrams. Also, the study suggests using multiple representations of scientific concepts to support the development of students' learning and thinking skills